2001
DOI: 10.1093/intimm/13.12.1533
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine regulates the IL-1β-induced cellular functions of human gingival fibroblasts

Abstract: In this study we examined the influence of adenosine on the cellular functions of human gingival fibroblasts (HGF), such as the production of inflammatory cytokines and extracellular matrices (ECM), and the expression and function of adhesion molecules. Concerning the expression of adenosine receptors, RT-PCR analysis revealed that HGF expressed adenosine receptor A1, A2a and A2b, but not A3 mRNA. Ligation of adenosine receptors by adenosine or its related analogue, 2-chloroadenosine (2-CADO), N(6)-cyclopentyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 37 publications
(55 reference statements)
2
46
0
Order By: Relevance
“…The A 1 R was shown to enhance leukocyte recruitment [6][7][8]10], phagocytosis [9], generation of reactive oxygen species and NO and cytokine production [7][8][9][31][32][33][34]. We have previously shown on PMCs and peritoneal leukocytes that A 1 R is up-regulated shortly after inoculation [13,14], and we now show that A 1 R is a potent promoter of inflammation in the peritoneum.…”
Section: Discussionmentioning
confidence: 67%
“…The A 1 R was shown to enhance leukocyte recruitment [6][7][8]10], phagocytosis [9], generation of reactive oxygen species and NO and cytokine production [7][8][9][31][32][33][34]. We have previously shown on PMCs and peritoneal leukocytes that A 1 R is up-regulated shortly after inoculation [13,14], and we now show that A 1 R is a potent promoter of inflammation in the peritoneum.…”
Section: Discussionmentioning
confidence: 67%
“…Human PDL (HPDL) cells, dental pulp (HDP) cells, gingival fibroblasts (HGFs), and gingival epithelial cells (HGEs) were cultured according to previously described methods (Murakami et al, 2001(Murakami et al, , 2002Shimabukuro et al, 2005Shimabukuro et al, , 2009). We previously established a mouse PDL cell line, MPDL22, and used this as described in our earlier publication (Yamada et al, 2007).…”
Section: Cell Culture and Induction Of Pdl Cell Cytodifferentiationmentioning
confidence: 99%
“…The precipitated RNA was resuspended in 0.1% diethylpyrocarbonate-treated distilled water. cDNA was synthesized and amplified via PCR as described previously (Murakami et al, 2001). Oligonucleotide PCR primers specific for hyaluronan synthase (HAS) 1, 2, 3, and HPRT mRNA were synthesized by Clontech (Palo Alto, CA, USA).…”
Section: Detection Of Hyaluronan Synthase 1-3 (Has1 Has2 and Has3) mentioning
confidence: 99%
“…Among the extracellular matrices, hyaluronan (HA) plays multi-functional roles in the growth and differentiation of cells during the course of inflammatory reactions and the process of wound-healing and regeneration in periodontal tissues (Shimabukuro et al, 2005). We previously reported that adenosine enhanced HAS mRNA expression in HGF, and that the expression was markedly abrogated by the AdoR antagonist XAC (Murakami et al, 2001). This also indicates that intracellular signaling via AdoR can be monitored by HAS mRNA expression in gingival fibroblasts.…”
Section: Regulation Of Has 1 Mrna Expression By Ecto-adenosine Deaminasementioning
confidence: 99%